Characterizing the U.S. Industrial Base for Coal-Powered Electricity - Samaras, Constantine (RAND Corporation, 2011)
To determine whether the industrial base for the U.S. domestic coal-based electricity generation industry can maintain the capability to design, construct, operate, and maintain coal-fired electricity generating units within reasonable cost, schedule, performance, environmental, and quality expectations, this book reviews interviews with stakeholders and data describing key elements of industry capability and validation or verification of concerns.